Beneficial effects of dietary organic acids on growth and health of juvenile Chinese mitten crab (Eriocheir sinensis) - Zhideng Lin; Yong Lei; Xiaodan Wang; Erchao Li; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Aquaculture Reports)
The present study determined the effects of five dietary organic acids on the growth and health status of juvenile Eriocheir sinensis. A control diet was without organic acids, and five experimental diets were supplemented with 0.2 % citric acid (CA), malic acid (MA), α-ketoglutaric acid (KG), fumaric acid (FA), and lactic acid (LA), respectively. The initial body weight of E. sinensis was 3.09 ± 0.01 g, and the experiment lasted eight weeks. The present study indicates that dietary CA, KG and FA can markedly improve growth performance and feed utilization for E. sinensis. In addition, all organic acids used in the present study, especially CA, KG and FA, promoted calcium (Ca) and phosphorus (P) deposition, possibly through increasing available P levels in the diet and up-regulating the gene expression of Ca and P absorption, leading to higher ash content of the whole body. Dietary CA, KG and FA significantly reduced whole-body total lipid content, suggesting that these organic acids may facilitate lipid utilization. Besides, all organic acids increased the activities of digestive enzymes, antioxidant enzymes and phosphatases. These results indicate that dietary organic acids benefit digestive ability, antioxidant state, and nonspecific immunity for juvenile E. sinensis. Considering the response of various indicators, we conclude that among the five tested organic acids, CA, KG, and FA have better potential as feed additives in the diets of E. sinensis.